PERKARA PERPINDAHAN WALI DARI WALI NASAB KEPADA WALI HAKIM KARENA WALI ADHOL (Studi Penetapan Perkara Nomor : 0097/ Pdt.P/ 2010/ PA. Kab. Kdr): (Studi Penetapan Perkara Nomor : 0097/ Pdt.P/ 2010/ PA. Kab. Kdr) - Ahmad Khotim (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2023)
Background. A woman who wants to marry a man must go through her parents (guardians) and with the consent of both, so that her household is in harmony with her parents' household. Don't let the newly built household have a bad impact on the parents, because the daughter marries a man her parents don't approve of. Therefore, it is appropriate to hand over the marriage to the guardian without forgetting the daughter's consent. Aim. This research was written to answer the questions outlined in two problem formulations, namely: (1)What is the reason for submitting a request for appointment as Wali Adhol to the Kediri Regency Religious Court (2) What is the judge's legal consideration regarding the granting or rejection of the application for appointment of adhol guardian Number: 0097/pdt.p/2010/PA.Kab.Kediri Methods. The problem approach method used in this research is a normative juridical approach model, namely an approach that focuses on the norms that apply and originate from juridical provisions. This means both from fiqh books, applicable laws and opinions from legal experts related to the issues the author discusses. Results. The reason the applicant's parents refused to become guardians was because they were following the wishes of their parents (the applicant's grandfather) that their child not marry someone from the same village. The judge's considerations in granting the application for the appointment of adhol guardians were because the parents' reasons for refusing to become guardians could not be justified either according to religion or law.